Administration of Palm Kernel Meal and íŸ-Mannanase on Laying Hens Productivity - Wicaksana, Dimas; Hidanah, Sri; Lokapirnasari, Widya Paramita; Al-Arif, Muhammad Anam; Lamid, Mirni; Suprianondo, Koesnoto (Universitas Airlangga, 2021)
The aim of this research was to observe the influence of palm kernel meal and íŸ-Mannanase on laying hens. Laying hens up to 2500 birds were reared in opened-house cage fed with commercial feed substituted with palm kernel meal and íŸ-Mannanase. All hens were divided into five groups in an order P0 as control group, groups without enzyme which are P1 with 7% palm kernel meal and P2 with 14% palm kernel meal, groups with íŸ-Mannanase which are P3 7% palm kernel meal and P4 with 14% palm kernel meal. The observed variables are feed intake, feed cost, egg weight, egg mass, feed conversion ratio, hen day production, and mortality rate. The results indicated that threr are no significant difference from all variables. The percentage of palm kernel meal for 14% with íŸ-Mannanase cannot give any influence on laying hens productivity.